FMR1 Intron 1 Methylation Predicts FMRP Expression in Blood of Female Carriers of Expanded FMR1 Alleles - Godler, David E. (American Society for Investigative Pathology, 2011)
Fragile X syndrome (FXS) is caused by loss of the fragile X mental retardation gene protein product (FMRP) through promoter hypermethylation, which is usually associated with CGG expansion to full mutation size (>200 CGG repeats). Methylation-sensitive Southern blotting is the current gold standard for the molecular diagnosis of FXS. For females, Southern blotting provides the activation ratio (AR), which is the proportion of unmethylated alleles on the active X chromosome. Herein, we examine the relationship of FMRP expression with methylation patterns of two fragile X–related epigenetic elements (FREE) analyzed using matrix-assisted laser desorption/ionization–time-of-flight mass spectrometry and the AR. We showed that the differential methylation of the FREE2 sequence within fragile X mental retardation gene intron 1 was related to depletion of FMRP expression. We also show that, using the combined cohort of 12 females with premutation (55 to 200 CGG repeats) and 22 females with full mutation alleles, FREE2 methylation analysis was superior to the AR as a predictor of the proportion of FMRP-positive cells in blood. Because matrix-assisted laser desorption/ionization–time-of-flight mass spectrometry is amenable to high-throughput processing and requires minimal DNA, these findings have implications for routine FXS testing and population screening.